Impact of reduced graphene oxide on the ethanol sensing performance of hollow SnO2 nanoparticles under humid atmosphere - Zito, Cecilia A. [UNESP]; Perfecto, Tarcísio M. [UNESP]; Volanti, Diogo P. [UNESP] (Elsevier, 2017)
The interference of humidity is a key factor to be considered in metal oxide semiconductors gas sensing performance. However, an efficient gas detection under humid conditions is a challenge. Herein, we report the effect of reduced graphene oxide (RGO) on volatile organic compounds (VOCs) sensing performance of hollow SnO2nanoparticles (NPs) under wet atmosphere. For this purpose, RGO-SnO2nanocomposite was obtained by a one-pot microwave-assisted solvothermal synthesis. The sensing tests for VOCs were conducted under dry air and at a relative humidity (RH) between 24 and 98%. The samples exhibited better response toward ethanol than to other VOCs such as acetone, benzene, methanol, m-xylene, and toluene, at the optimum operating temperature of 300 °C. Furthermore, RGO-SnO2nanocomposite showed an enhanced ethanol response in comparison with pure hollow SnO2NPs. Even under 98% of RH, the RGO-SnO2nanocomposite showed a response of 43.0 toward 100 ppm of ethanol with a response time of 8 s. The excellent sensor performance is related to the hollow structure of SnO2NPs, and the heterojunction between RGO and SnO2. Therefore, the RGO content can be a promising approach to minimize the humidity effect on SnO2ethanol sensing performance.
Keywords: Humidity; Nanocomposites; One-pot synthesis; Oxolation; Reduced graphene oxide; Tin oxide